A guided internet-delivered mindfulness-based cognitive therapy for insomnia: study protocol for a randomized controlled study - Zeng, Zixuan; Liu, Fei; Zhu, Chenyi; Long, Xiangyun; Jiang, Jiahui; Huang, Lei; Lu, Zheng (Frontiers in Psychiatry, 2025)
BackgroundChronic insomnia disorder (CID) is highly prevalent and impacts individuals’ physiological, psychological and social functions. Although cognitive behavioral therapy for insomnia (CBT-I) is the recommended first-line treatment option for CID, approximately 20% of patients still exhibit limited effectiveness. The literature has shown that mindfulness can benefit CBT-I protocols and that mindfulness-based cognitive therapy (MBCT) is effective in treating insomnia. However, the effectiveness of therapist-guided internet-based MBCT-I (iMBCT-I) has not yet been tested.ObjectiveThis study protocol aims to evaluate the effect of therapist-guided iMBCT-I on chronic insomnia among Chinese adults.MethodsThis will be a two-armed, parallel group, randomized controlled study with 80 CID patients. The participants will be randomized to either the iMBCT-I program or the sleep hygiene education (SHE) program at an allocation ratio of 1:1 via simple randomization. Assessments will be carried out at baseline, at the end of the intervention (week 8) and at the follow-up time (week 20). The primary outcome was insomnia severity at week 8. Statistical analyses will follow the intention-to-treat (ITT) principle.DiscussionThis is the first study to investigate the effectiveness of therapist-guided iMBCT-I in CID patients. Should it be effective, this study will provide evidence for clinical practitioners, therapists and patients to consider a new psychotherapeutic option and for technicians to perform self-guided iMBCT-I applications in the future.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR240008430.